Tip Nuances for the Nose of African Descent - Chike-Obi, Chuma J.; Boahene, Kofi; Bullocks, Jamal M.; Brissett, Anthony E. (Facial Plastic Surgery, 2012)
Patients of African descent are seeking rhinoplasties today more than ever. As a result, the rhinoplasty surgeon must be aware of the ethnic, cultural, anatomic, and surgical issues pertaining to this patient population. In this article, the nuances of rhinoplasty as it pertains to the nasal tip in patients of African descent are discussed.
Keywords: rhinoplasty; ethnic; nasal tip; African; African-American